Functional gastrointestinal disorders, mental health, genetic susceptibility, and incident chronic kidney disease - Mengyi Liu; Panpan He; Ziliang Ye; Sisi Yang; Yanjun Zhang; Qimeng Wu; Chun Zhou; Yuanyuan Zhang; Fan Fan Hou; Xianhui Qin; Jinjiao Li; Yuanyuan Ji (Chinese Medical Journal, 2024)
Abstract. Background:. Whether functional gastrointestinal disorders (FGIDs) are associated with the long-term risk of chronic kidney disease (CKD) remains unclear. We aimed to investigate the prospective association of FGIDs with CKD and examine whether mental health mediated the association. Methods:. About 416,258 participants without a prior CKD diagnosis enrolled in the UK Biobank between 2006 and 2010 were included. Participants with FGIDs (including irritable bowel syndrome [IBS], dyspepsia, and other functional intestinal disorders [FIDs; mainly composed of constipation]) were the exposure group, and non-FGID participants were the non-exposure group. The primary outcome was incident CKD, ascertained from hospital admission and death registry records. A Cox proportional hazard regression model was used to investigate the association between FGIDs and CKD, and the mediation analysis was performed to investigate the mediation proportions of mental health. Results:. At baseline, 33,156 (8.0%) participants were diagnosed with FGIDs, including 21,060 (5.1%), 8262 (2.0%), and 6437 (1.6%) cases of IBS, dyspepsia, and other FIDs, respectively. During a mean follow-up period of 12.1 years, 11,001 (2.6%) participants developed CKD. FGIDs were significantly associated with a higher risk of incident CKD compared to the absence of FGIDs (hazard ratio [HR], 1.36; 95% confidence interval [CI], 1.28–1.44). Similar results were observed for IBS (HR, 1.27; 95% CI, 1.17–1.38), dyspepsia (HR, 1.30; 95% CI, 1.17–1.44), and other FIDs (HR, 1.60; 95% CI, 1.43–1.79). Mediation analyses suggested that the mental health score significantly mediated 9.05% of the association of FGIDs with incident CKD and 5.63–13.97% of the associations of FGID subtypes with CKD. Specifically, the positive associations of FGIDs and FGID subtypes with CKD were more pronounced in participants with a high genetic risk of CKD. Conclusion:. Participants with FGIDs had a higher risk of incident CKD, which was partly explained by mental health scores and was more pronounced in those with high genetic susceptibility to CKD.